3x-6(x+6)=-66

Simple and best practice solution for 3x-6(x+6)=-66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6(x+6)=-66 equation:


Simplifying
3x + -6(x + 6) = -66

Reorder the terms:
3x + -6(6 + x) = -66
3x + (6 * -6 + x * -6) = -66
3x + (-36 + -6x) = -66

Reorder the terms:
-36 + 3x + -6x = -66

Combine like terms: 3x + -6x = -3x
-36 + -3x = -66

Solving
-36 + -3x = -66

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + -3x = -66 + 36

Combine like terms: -36 + 36 = 0
0 + -3x = -66 + 36
-3x = -66 + 36

Combine like terms: -66 + 36 = -30
-3x = -30

Divide each side by '-3'.
x = 10

Simplifying
x = 10

See similar equations:

| -3(6+7)x=171 | | 5x^2+42=2x^2+117 | | 6x^2+9x-8=0 | | 7(1x+3)=105 | | A+B+15=45 | | 7x+2(4x+8)=4 | | 7+10n=37 | | -8+6(3g+6)= | | 180=y-4 | | -3x-8y+20y=5x+19 | | 4x^2-2x-120=0 | | 11x-4=11+2 | | 4(-5x-6)=-4 | | x/5+17=20 | | 2(7-4x)=-74 | | 9y^2+27y+14= | | 7(-7x+8)=-483 | | 12x+23=71 | | x^3=167 | | 17.00+5.50h=11.00+6.75h | | 98=7x-7 | | 4y-5y=81 | | 10+4c=5(c-6)+33 | | 5+(-24)= | | 2.5d+7.75=4+3.25d | | 6(x+3)-4(x-3)= | | 3w^2(w^2+3)=8+7w^2 | | 13x+2=54 | | 835=5x^3 | | 360=106+84+y+38+3y+12 | | 5+7*5+5= | | 4x-8=4x+-36 |

Equations solver categories